SUMBANGSIH WERDA NOTARIS DALAM ORGANISASI IKATAN NOTARIS INDONESIA - Laurensius Arliman S (Yuridika, 2015)
Notary joins an organization called Indonesian Notaries Association. Indonesian Notary Association membership consists of ordinary members, active and werda notary; Extraordinary Members, any person who has passed the master degree of notary or special notary education programs and registered as members of the association; and Honorary Member. werda active role in the indonesian notaries association, namely: 1) role views of the rights and obligations as a regular member Indonesian notaries association; 2) their role in the Congress; 3) their role in the Regional Conference; 4) role in Regional Conference. werda Notary from the point of legal logic, who no longer holds a notary protocol, if called upon by law enforcement for the purposes of the examination with regard to the deeds made Notary Law. If summoned by law enforcement for the purpose of examination relating to the deeds he / she has ever made in a criminal case, the provisions of Article 66 of the Notary Office Law shall apply.